Understanding the Economic Impacts of Greenhouse Gas Mitigation Policies on Shipping : What Is the State of the Art of Current Modeling Approaches? - Halim, Ronald A.; Smith, Tristan; Englert, Dominik (World Bank, Washington, DC, 2019)
The International Maritime Organization's initial strategy on reduction of greenhouse gas emissions from ships stipulates that the international shipping sector should assess the impacts on states prior to adoption of the mitigation measures included in the strategy. This assessment should be undertaken as a matter of urgency, and disproportionately negative impacts should be assessed and addressed as appropriate. This paper aims to contribute to this discussion by reviewing the state-of-the-art research on the economic impacts of greenhouse gas mitigation measures on states, using model-based analysis. Specifically, the paper: (i) identifies four areas of economic impacts and their relationships, (ii) compiles the latest findings on the estimated magnitudes of these impacts, and (iii) presents relevant modeling approaches along with best practices for selecting and applying these approaches in impact assessments.The paper concludes that introducing greenhouse gas mitigation measures, such as carbon prices applied to bunker fuels in the range of 10 to 50 USD/ton of carbon dioxide, might increase maritime transport costs by 0.4 percent to 16 percent. However, this would only marginally increase the import prices of goods (by less than 1 percent). For transport choices, the increased cost of maritime transport induced by greenhouse gas mitigation measures might only slightly reduce the share of maritime transport, by 0.16 percent globally. Furthermore, a global carbon tax applied to all transport modes might stimulate a shift toward maritime transport from all other modes. The impacts of a carbon price in the range of 10 to 90 USD/ton of carbon dioxide on national economies are expected to be modest (−0.002 percent to −1 percent of GDP).